The Dynamics of Training and Development Initiatives: Unraveling their Influence on Organizational Performance - Ammad Zafar (International Journal of Experiential Learning & Case Studies)
The research proposed by this study explores the relationship between training and development (T&D) and the organization's performance with special reference to the corporate sector of Karachi. The premise for this research, therefore, lies in the understanding that the subject of employee development has been accepted as a key factor in the promotion of organizational effectiveness and efficiency and the attainment of competitive advantage within the complex business environment of the modern world. The study employed quantitative and qualitative data. The quantitative data is collected through closed ended question questionnaire based on five-point Likert scale the respondent were selected though convenience sample and analysed through SPSS and Smart PLS. The qualitative data is collected from a review of past relevant research papers from repositories and open-access journals, 102 respondents were interviewed during a survey conducted electronically. The study reveals the substantial positive interaction between organizational performance and T&D programs, highlighting the potential for significant improvement and instilling a sense of hope and optimism. According to the study, there is an urgent and compelling need for the corporate sector of Karachi to strategically focus on the training and development of people in order to support organizational growth and development. Training is a powerful tool and opens up several Seiten of learning and development besides increasing motivation and commitment to work that, in turn, has a direct impact on productivity. Further, to confirm the importance of T&D programs in sustainable growth and competitive advantage strategy, this study is quite appropriate through better focus, attention and development of its human capital, which is likely to result in the sustainable growth of the organization in the complex business environment of Karachi and other areas of the world.